Routledge handbook of adapted physical education - Haegele, Justin A.; Hodge, Samuel R.; Shapiro, Deborah R. (Deborah Rebecca) (Routledge international handbooks, 2020)
This handbook represents the first comprehensive and evidence-based review of theory, research, and practice in the field of adapted physical education (APE). Exploring philosophical and foundational aspects of APE, the book outlines the main conceptual frameworks informing research and teaching in this area, and presents important material that will help shape best practice and future research. Written by world-leading researchers, the book introduces the key themes in APE, such as historical perspectives on disability, disability and the law, language, and measurement. It examines the most significant theoretical frameworks for understanding APE, from embodiment and social cognitive theory to occupational socialization, and surveys current debates and practical issues in APE, such as teacher training, the use of technology, and physical inactivity and health. Acknowledging the importance of the voices of children, parents and peers, the book also explores research methods and paradigms in APE, with each chapter including directions for further research. Offering an unprecedented wealth of material, the Routledge Handbook of Adapted Physical Education is an essential reference for advanced students, researchers and scholars working in APE, and useful reading for anybody with an interest in disability, physical education, sports coaching, movement science or youth sport.